Chapter Terezín und Jasenovac - Umkämpfte Gedenkstätten vor und nach 1989 - Radonić, Ljiljana (Medien und kulturelle Erinnerung, 2020)
This volume examines memory narratives in literature, television, film, photography, and museum exhibitions that, firstly, take a transmedial approach and, secondly, narrate and de/construct the past or pasts in Central Europe in different ways, nationally and/or transnationally. It also discusses the connections between various media and questions understandings of the trans-/national.